Understanding the MetaBirkin: Trademark Law and an Appropriate Legal Standard for NFTs - Gery, Michelle (The Columbia Journal of Law & the Arts, 2024)
This note argues that the recently decided trademark case, Hermès v. Rothschild, highlighted the flaws of the Polaroid factors and their singular focus on determining consumer confusion, and makes a case for an expanded understanding of a copyright fair use defense in trademark law. Two forms of fair use are already acknowledged in the trademark context, but neither are comparable to the much stronger fair use exception in copyright law. The factors in the copyright fair use defense seem to strike directly at the heart of the most salient concerns in Hermes v. Rothschild, while the Polaroid factors seem to allow only tangential considerations of certain key factors.